2012
DOI: 10.1039/c2nr31290e
|View full text |Cite
|
Sign up to set email alerts
|

Surface engineering of gold nanoparticles for in vitro siRNA delivery

Abstract: Cellular uptake, endosomal/lysosomal escape, and the effective dissociation from the carrier are a series of hurdles for specific genes to be delivered both in vitro and in vivo. To construct siRNA delivery systems, poly(allylamine hydrochloride) (PAH) and siRNA were alternately assembled on the surface of 11.8 ± 0.9 nm Au nanoparticles (GNP), stabilized by denatured bovine serum albumin, by the ionic layer-by-layer (LbL) self-assembly method. By manipulating the outmost PAH layer, GNP-PAH vectors with differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 43 publications
0
63
0
1
Order By: Relevance
“…These, in turn, may be loaded with anionic polymeric species, thanks to electrostatic interactions. In this connection, PAHcoated nanoparticles have been proposed for efficiently loading siRNA drugs in anticancer therapies [33,34]. Being involved in a long term research project for the use of siRNA against hepatocarcinoma, we also included GNS/PEGCOOH further coated with PAH in this study.…”
Section: Coated Gnsmentioning
confidence: 99%
See 1 more Smart Citation
“…These, in turn, may be loaded with anionic polymeric species, thanks to electrostatic interactions. In this connection, PAHcoated nanoparticles have been proposed for efficiently loading siRNA drugs in anticancer therapies [33,34]. Being involved in a long term research project for the use of siRNA against hepatocarcinoma, we also included GNS/PEGCOOH further coated with PAH in this study.…”
Section: Coated Gnsmentioning
confidence: 99%
“…the PAH@GNS/PEGCOOH constructs, see Fig. 2, as PAH is a cationic polymer frequently used for enveloping nanoparticles and further loading the negatively charged NABDs (nucleic acid based drugs) [33,34]. In this perspective, we also checked the ability of the latter construct to be further loaded with a model anionic polymer, polystyrene sulfonate (PSS), see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, poly(allylamine hydrochloride) (PAH) has been used for different types of siRNA delivery constructs in order to overcome these barriers [35,125]. An LbL strategy has recently been reported in which bovine serum albumin (BSA) was first reduced by NaBH4, which resulted in denatured BSA (dBSA) [116]. This dBSA carried 35 thiol groups that were used for capping AuNPs [116].…”
Section: Layer-by-layer Self-assemblymentioning
confidence: 99%
“…An LbL strategy has recently been reported in which bovine serum albumin (BSA) was first reduced by NaBH4, which resulted in denatured BSA (dBSA) [116]. This dBSA carried 35 thiol groups that were used for capping AuNPs [116]. Due to the presence of numerous carboxyl groups on dBSA, dBSA-AuNPs were electrostatically coated with PAH to form a cationic layer (PAH-dBSA-AuNPs), which could efficiently bind siRNA (siRNA-PAHdBSA-AuNPs).…”
Section: Layer-by-layer Self-assemblymentioning
confidence: 99%
“…When verifying protein knockdown, alternative techniques would need to be used such as western blots [143], flow cytometry [45] and In-Cell westerns [144]. A recent study by Zhao et al reported the development of AuNPs loaded with siRNA against the epidermal growth factor receptor (EGFR) gene, and observed a knockdown efficiency of between 16-38% in MCF- 7 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 REVIEW NANO TODAY 33 cells via flow cytometry (Figure 16) [145]. The use of the flow cytometer allowed for the distinction between populations of cells, with a better assessment of the siRNA knockdown; in contrast to western blots, which use a pooled protein sample from a cellular population.…”
Section: The Protein Levelmentioning
confidence: 99%